DNA sequence of the tandem ribosomal RNA promoter for B. subtilis operon rrnB. - Stewart, G C (1983)
A new ribosomal RNA operon designated rrnB has been identified by screening a Charon 4a library of cloned B. subtilis sequences. Clones containing the promoter region of this operon are unstable in E. coli unless a special vector possessing a transcriptional terminator is used. DNA sequence data suggests that this operon contains two tandem putative promotor regions not unlike those found in E. coli. There are 92 base pairs separating the two "-10 regions" of the promotors. The second is 180 bp upstream from the start site for mature 16S RNA. A potential 29 base pair stem structure necessary for processing of the mature 16S RNA sequence can also be predicted from this analysis.